2022
DOI: 10.1136/jnis-2022-019240
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of flow diversion for unruptured intracranial aneurysms: a systematic review and meta-analysis

Abstract: BackgroundFlow diverters have been widely used in clinical practice for more than a decade. However, most outcome data are limited to 1 year timepoints. This study aims to offer meta-analysis data on long-term (>1 year) safety and effectiveness results for patients with aneurysms treated with flow diverters.MethodsPubMed, Web of Science, Embase, and SCOPUS were searched up to February 24, 2022 using the AutoLit platform. We included primary studies assessing the long-term outcomes for flow diverter devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…They criticise that this recommendation is based on what they describe as 'a single small prospective study' and 'small exploratory study', 3 and state that 'in the meantime a plethora of retrospective and prospective controlled data is available demonstrating overwhelming safety and efficacy of flow diverting stents', referring to the review mentioned above. 2 Since we had not found any controlled studies in our systematic review of the literature, we read with interest the studies referenced in this systematic review. To our disappointment none of the 11 studies included in the review had a control group.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They criticise that this recommendation is based on what they describe as 'a single small prospective study' and 'small exploratory study', 3 and state that 'in the meantime a plethora of retrospective and prospective controlled data is available demonstrating overwhelming safety and efficacy of flow diverting stents', referring to the review mentioned above. 2 Since we had not found any controlled studies in our systematic review of the literature, we read with interest the studies referenced in this systematic review. To our disappointment none of the 11 studies included in the review had a control group.…”
mentioning
confidence: 99%
“…We are delighted to read that the ESO guidelines on management of unruptured intracranial aneurysms have attracted attention, 1 and we thank Drs Bendszus and Möhlenbruch for drawing our attention to a systematic review of the literature that has become available after publication of the guidelines. 2 Drs Bendszus and Möhlenbruch challenge our suggestion to use flow diverting stents as a treatment option only if no other endovascular or microsurgical options are available to occlude the aneurysm at a risk lower than the expected 5-year risk of rupture and if the risk of rupture outweighs the risk of treatment with flow diverting stents. They criticise that this recommendation is based on what they describe as 'a single small prospective study' and 'small exploratory study', 3 and state that 'in the meantime a plethora of retrospective and prospective controlled data is available demonstrating overwhelming safety and efficacy of flow diverting stents', referring to the review mentioned above.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple questions currently remain in the FD literature; these include the long-term efficacy of the different devices and whether there are any safety/efficacy differences between these devices. A recent systematic review reported a pooled 5-year complete occlusion rate of 96% with most of the literature studies using PED 14 ; however, the analysis did not account for the different FD devices nor particular aneurysmal location, and further studies on this remain warranted. Moreover, limited data are currently known regarding which aneurysm type might be suited for each of those devices and head-to-head comparative performance data of the different devices in certain aneurysms location, for which prospective trials would be needed.…”
mentioning
confidence: 99%
“…FD stents were initially designed and licensed for large, intracranial, and unruptured ICA aneurysms. 5 To this end, FDs have also been combined with coiling for ruptured or unruptured aneurysms [7][8][9] and blister-like/dissecting aneurysms. 10 Although van Rooij et al 11 considered EVT dangerous and not yet an alternative for unruptured ICA aneurysms in 2013, EVT is now preferred as first-line treatment in many centers.…”
mentioning
confidence: 99%